Diagnostic Study of Pathogenic Bacterial Isolated from Camel’s Pneumonic lungs Slaughtered in Al-Muthanna Province Abattoir, Iraq Using Vitek2 Compactiological approach and Vitek2 compact in Al- Muthanna province - M Watban, Hayder; M Al-Maaly, Nabeel (The Iraqi Journal of Veterinary Medicine, 2024)
The bacterial etiologies of pneumonia in camels represent a rising health concern, with camels being healthy during antemortem examination despite significant losses in production and mortality attributed to maladies identified only upon postmortem evaluation. A cross-sectional study was undertaken at an abattoir, spanning the period from October 2022 to March 2023, to examine gross pathological disorders and identify bacterial pathogens in the respiratory system (specifically the lungs) of camels (Camelus dromedaries) suspected of having pneumonia. A total of 100 dromedary camels slaughtered in Al-Muthanna abattoir were examined. Postmortem examination was performed to identify any gross changes in camels’ lungs. Then, the swab samples were obtained from lungs and submitted to bacteriological cultures on both general and selective media. Additionally, microscopic examination of the bacteria using Gram staining followed by diagnosis with Vitek 2‎ system. The number of Gram-negative bacterial species isolated from camel lungs was 74 isolates, distributed as 31 (41.89%) of Klebsiella pneumoniae, 26 (35.13%) of Escherichia coli and 17 (22.97%) of Pseudomonas aeruginosa. This study suggests that K. pneumoniae exhibited a higher infection rate compared to E. coli and P. aeruginosa in pneumonic camels slaughtered at the Al-Muthanna abattoir‎‎‎‎‎.